Post Operative Systolic Pressure Ratio between Right and Left Ventricle Predicts Early Outcome after Total Correction of Tetralogy of Fallot - Ahmed, AT Shahrier; Hasan, Md Kamrul; Karim, Md Rezaul (University Heart Journal, 2018)
PRV/LV can be easily measured in the operating room by which we can assess the adequacy of relief of pulmonary stenosis. A number of studies carried out where PRV/LV ratio 0.7 was taken as cut off point however in this study post repair ratio 0.5 was taken as cut off value because a recent study has shown better outcome after total correction of tetralogy of Fallot when the post repair PRV/LV was below .05. When the ratio is above 0.5, some extra precaution may be needed in the post operative period to reduce the morbidity and mortality. University Heart Journal Vol. 13, No. 2, July 2017; 59-61